Using Data-Limited Methods to Assess the Status of Bartail Flathead Platycephalus indicus Stocks in the Bohai and Yellow Seas - Zheng, Lei; Wang, Yuanchao; Liu, Shude; Liang, Cui; Xian, Weiwei (Frontiers in Marine Science, 2022)
We applied Catch and Maximum Sustainable Yield (CMSY), Bayesian Schaefer model (BSM), and Abundance Maximum Sustainable Yield (AMSY) methods to estimate the status of Platycephalus indicus stocks in the Bohai and Yellow Seas, assessed model performance, and determined the impact of priors derived from expert knowledge on the performance of each model. Results showed that P. indicus stock in the Bohai Sea had collapsed, while that in the Yellow Sea stock was recovering. With the input of an expert prior derived from the length-based Bayesian biomass (LBB) estimation method, the CIs of each model narrowed, but the changes in biomass trajectory were not significant, and the estimates of B/BMSY were differed compared with model results using default rules. These three models can be used to evaluate data-limited stocks to reflect stock dynamics when reliable inputs are available. However, the ranges of priors, which are preferably obtained from other stock assessment tools, should be carefully established.